CABCOCO1, a novel coiled‐coil protein With calcium‐binding activity, is localized in the sperm flagellum. Issue 10 (28th March 2016) - Kawashima, Akihiro; Kigoshi, Takumi; Katoh, Yuki; Ishikawa, Yu; Shawki, Hossam H.; Inoue, Naoya; Tamba, Michiko; Matsuda, Manabu; Okamura, Naomichi
SUMMARY: The gene 1700040L02Rik (GenBank accession number NM_028491, NP_082767.1) was selected by in silico screening as candidate that encodes a calcium‐binding protein in sperm from a database of predicted mouse cilia‐related genes. The predicted amino acid sequence revealed the presence of coiled‐coil domain at the C‐terminus and a CLAMP motif containing a leucine zipper domain in the middle of the protein. Assessment of a recombinant version of this protein by Stains‐all and ruthenium red staining and by direct measurement of terbium binding revealed its calcium‐binding activities. We therefore named this protein CABCOCO1 for calcium‐binding coiled‐coil protein‐1. Immunohistochemical analyses showed its localization in spermatogenic cells of mouse testis. CABCOCO1 was first observed in the cytoplasm of murine spermatocytes, concentrated around centrioles of spermatids and co‐localized with the centrosomal protein pericentrin. During the stage when centrosome number is reduced, CABCOCO1 relocalized to the murine sperm flagellum. On the other hand, in porcine sperm, whose proximal centriole remains intact while the distal centriole degenerates during spermiogenesis, CABCOCO1 localized both in the basal body and the flagellum. These results suggested that CABCOCO1 is involved in the control of sperm flagellar movement. Mol. Reprod. Dev. 83: 912–926, 2016 © 2016 Wiley Periodicals, Inc .